DDT and the Insect Problem - Leary, James C.; Fishbein, William I.; Salter, Lawrence C. (McGraw-Hill Book Company, 1946)
Volume dedicated to summarizing the various uses, chemistry, pharmacology, history, and methods of using DDT. DDT (dichloro-diphenyl-trichloroethane) was developed as a synthetic insecticide in the 1940s. It was initially used to combat malaria, typhus, and other insect-borne diseases. The EPA banned DDT in 1972 after research showed harmful impacts to wildlife and potential human health risks. Frontmatter and selected illustrations have been digitized. This work is protected by copyright law; to view the full text, contact or visit the Othmer Library of Chemical History.
Keywords: DDT (Insecticide)